Side Effects of Misoprostol Per Rectal for Treating Postpartum Hemorrhage in Vaginal Delivery versus Cesarean Section: What Do We Know So Far? Efek Samping Misoprostol Per Rektal untuk Pengobatan Perdarahan Pascasalin - Novitasari Nasution; Hesty U. Ramadaniati; Syamsudin Syamsudin; Ajeng Normala (Indonesian Socety of Obstetrics and Gynecology, 2020)
Objective: To compare the incidence and profiles of misoprostol’ side effects given per rectal for treating postpartum haemorrhage in vaginal delivery versus cesarean section.Methods: A prospective observational study involving 40 women delivered by vaginal birth (VD) and 40 by cesarean section (CS) was undertaken in a gynecology ward of a hospital in West Java. The incidence of misoprostol’s side effects was identified through patient observation and medical note review. The side effect probability was rated by the panellists of healthcare providers. Patient characteristics and side effect data were summarized descriptively. The incidence rates of misoprostol’s side effect between the two groups were compared using Z-test.Results: Thirty-four patients (85.0%) in the VD group experienced side effects, whilst all CS patients reported at least one side effect. There was no significant difference in the proportion of patients having side effects in the two groups (p=0.366). There were 135 and 164 side effects in the VD group and CS group, respectively. There was no discernible difference in side effect profile between the two groups. Gastrointestinal side effects accounted for the most frequent side effects. Regarding the side effect probability, the panellists rated all side effects in VD patients as probable. Meanwhile, around70% of side effects in CS patients were regarded as probable leaving the remaining as definite.Conclusion: High incidence of misoprostol’s side effects was documented both in VD and CS patients. The incidence rates and side effect profile between the two delivery modes were quite similar.Keywords: cesarean section, misoprostol, postpartum haemorrhage, side effect, vaginal delivery Abstrak Tujuan:Membandingkan insiden dan profil efek samping misoprostol per rektal untuk pengobatan perdarahan pascasalin pada persalinan pervaginam versus seksio sesarea.Metode: Penelitian observasional prospektif melibatkan 40 perempuan yang melahirkan melalui persalinan pervaginan (VD) versus 40 pasien melalui seksio sesarea (CS) dilakukan di bangsal ginekologi sebuah rumah sakit di Jawa Barat. Insiden efek samping misoprostol diidentifikasi melalui pengamatan pasien dan kajian rekam medis. Probabilitas efek samping dinilai oleh panel tenaga kesehatan. Karakteristik pasien dan profil efek samping dianalisis secara deskriptif. Proporsi insiden efek samping misoprostol antara dua metode persalinan dibandingkan menggunakan uji Z.Hasil :Tiga puluh empat pasien (85,0%) pasien di kelompok VD mengalami efek samping, sementara semua pasien CS melaporkan setidaknya satu efek samping. Tidak ada perbedaan yang signifikan terkait proporsi pasien yang mengalami efek samping di kedua kelompok (p=0,366). Secara keseluruhan terdapat 135 dan 164 efek samping pada kelompok VD dan CS secara berurutan. Tidak ada perbedaan yang nyata dalam profil efek samping kedua kelompok. Efek samping terkait saluran cerna merupakan efek samping yang palings sering ditemukan. Terkait probabilitas kejadian efek samping, panelis menilai semua efek samping pada kelompok VD sebagai “mungkin”. Sementara itu, sekitar 70% efek samping pada pasien CS dikategorikan “mungkin” dan selebihnya “sangat mungkin”.Kesimpulan :Insiden tinggi efek samping misoprostol ditemukan baik pada pasien VD maupun CS. Proporsi insiden dan profil efek samping cukup seragam pada dua kelompok tersebut.Kata kunci: efek samping, misoprostol, perdarahan pascasalin, persalinan pervaginam, persalinan seksio sesarea